Possible involvement of AMP-activated protein kinase in obesity resistance induced by respiratory uncoupling in white fat - Matejkova, Olga; Mustard, Kirsty J; Sponarova, Jana; Flachs, Pavel; Rossmeisl, Martin; Miksik, Ivan; Thomason-Hughes, Michaela; Grahame Hardie, D; Kopecky, Jan (FEBS letters, 2004)
The AMP-activated protein kinase (AMPK) cascade is a sensor of cellular energy charge that promotes catabolic and inhibits anabolic pathways. However, the role of AMPK in adipocytes is poorly understood. We show that transgenic expression of mitochondrial uncoupling protein 1 in white fat, which induces obesity resistance in mice, is associated with depression of cellular energy charge, activation of AMPK, downregulation of adipogenic genes, and increase in lipid oxidation. Activation of AMPK may explain the complex metabolic changes in adipose tissue of these animals and our results support a role for adipocyte AMPK in the regulation of storage of body fat.
Keywords: Carrier Proteins; přirozená imunita; Ion Channels; DNA primery; Base Sequence; Obesity; transportní proteiny; Animals, Genetically Modified; Oxidation-Reduction; Immunity, Innate; Adenylate Kinase; myši; Reverse Transcriptase Polymerase Chain Reaction; Uncoupling Protein 1; adenylátkinasa; Mice; Oleic Acid; obezita; tuková tkáň; Skin; geneticky modifikovaná zvířata; uncoupling protein 1; mužské pohlaví; mitochondriální proteiny; Adipose Tissue; polymerázová řetězová reakce s reverzní transkripcí; membránové proteiny; zvířata; kůže; Mice, Inbred C57BL; iontové kanály; oxidace-redukce; Membrane Proteins; Animals; spotřeba kyslíku; Male; epididymis; kyselina olejová; Epididymis; sekvence nukleotidů; myši inbrední C57BL; Oxygen Consumption; Mitochondrial Proteins; DNA Primers